2015
DOI: 10.1007/s11468-015-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Broadband Tunable Properties of Surface Plasmon Resonances of Noble Metal Nanoparticles Using Mie Scattering Theory: Plasmonic Perovskite Interaction

Abstract: We suggest semi-analytical approach to study the optical properties of noble metal nanoparticles and their interaction to the perovskite material (methyl ammonia lead halide: CH 3 NH 3 PbI 3 ). Metal nanoparticles embedded in perovskite matrix exhibits broadband surface plasmon resonances, and the tunability of these plasmonic resonances is highly sensitive to particle size. The calculation of optical cross section have been done using Mie scattering theory which is applicable to arbitrary size and spherical-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The enhanced absorption results arose from both the plasmonic near-field and scattering effects. Pathak et al calculated the optical cross-section of arbitrarily sized and spherical-shaped metal NPs with perovskite by Mie scattering theory 80 . They found that NPs with a radius of 15 nm and volume concentration of approximately 10% achieved the highest scattering efficiency.…”
Section: Plasmonic–perovskite Solar Cellsmentioning
confidence: 99%
“…The enhanced absorption results arose from both the plasmonic near-field and scattering effects. Pathak et al calculated the optical cross-section of arbitrarily sized and spherical-shaped metal NPs with perovskite by Mie scattering theory 80 . They found that NPs with a radius of 15 nm and volume concentration of approximately 10% achieved the highest scattering efficiency.…”
Section: Plasmonic–perovskite Solar Cellsmentioning
confidence: 99%
“…The computation of electric field has been done by using COMSOL Multiphysics software with triangular fine grid. The red region shows the high-intensity zone which can be utilized for various applications [11][12][13][14][15].…”
Section: Extinction Cross Section Of Silver and Gold Nanosphere: Semimentioning
confidence: 99%
“…More specifically, both N.K. Pathak et al [18] and Roopak et al [19] explored Mie theory [20] and showed that silver, gold and aluminum nanoparticles, embedded inside a perovskite matrix, support plasmonic resonances of high magnitude with tunable resonance frequency and width by varying the size, shape or material. These results are very promising since plasmonic nanoparticles can induce light incoupling to the perovskite near its band edge (~650-800 nm) where it shows inferior photo response due to lower absorption in conjunction with increased reflection from the perovskite at that regime [6], [7].…”
Section: Introductionmentioning
confidence: 99%